Capacity Development for Geospatial Data Management in the Public Works Sector in Bulukumba Regency - Irwan .; Mimi Arifin; Abdul Rachman Rasyid; Venny Veronica Natalia; Laode Muh Asfan Mujahid; Jayanti Mandasari Andi Munawarah Abduh; Suci Anugrah Yanti; Dewa Sagita Alfadin Nur; Sri Wahyuni (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
In the era of digital government transformation, the utilization of geospatial data has become pivotal for accurate, efficient, and integrated planning, monitoring, and evaluation of infrastructure development. However, the capacity of human resources—particularly within the Office of Public Works and Spatial Planning (PUTR) of Bulukumba Regency—in managing geospatial data remains limited. This constraint may hinder the optimization of location-based decision-making in public infrastructure development. In fulfillment of the university’s third pillar of higher education—community service—the Department of Urban and Regional Planning at Hasanuddin University conducted a collaborative community engagement activity under the Faculty of Engineering’s Community Service Learning Program (LBE). The initiative focused on enhancing the geospatial data management capacity of local government officials. The activity was held on September 15, 2025, at the PUTR Office of Bulukumba Regency and involved technical staff and geospatial data officers. The methodology combined theoretical instruction with hands-on simulation, including field data collection using mobile devices and point mapping, followed by spatial data processing using freely accessible Geographic Information System (GIS) software. The results indicate that participants demonstrated high engagement and successfully acquired foundational competencies in geospatial data management. Furthermore, the activity fostered strategic academic–government collaboration, opening avenues for joint research, the development of a regional geospatial information system (SIGD), and ongoing technical mentoring. Thus, this initiative not only strengthened local institutional capacity but also laid the groundwork for sustainable, data-driven infrastructure planning in Bulukumba Regency.